Does School Connectedness Mediate the Relationship between Teacher Support and Depressive Symptoms?. Issue 1 (14th November 2018) - Joyce, Hilary D
Abstract: Strong teacher support is associated with and predictive of fewer depressive symptoms among youths. However, school connectedness may play a role in explaining this relationship. Using the National Longitudinal Study of Adolescent to Adult Health, this study examined the mediating role of school connectedness on the relationship between teacher support and depressive symptoms in adolescents. The findings showed that school connectedness partially mediated the relationship between depressive symptoms and both feeling cared about by teachers and getting along with teachers. The study findings offer important implications for school social workers who may play an important role in strengthening student–teacher relationships and promoting strategies that enhance student connection to schools.